Assessment of occupational exposure in medical practice in Gabon during 2013–2020 - P. Ondo Meye; S.Y. Loemba Mouandza; G.B. Dallou; Y. Omon; B.C. Mabika Ndjembidouma; C. Chaley; G.H. Ben-Bolie (Radiation Medicine and Protection, 2023)
Objective: To evaluate whole-body, extremity and eye-lens occupational dose equivalents of ionizing radiation to Occupationally Exposed Workers (OEWs) in Gabon, monitored by the national Individual Monitoring Service (IMS), in the medical practice. Methods: A total of 816 dose records for 205 OEWs were evaluated. Doses were collected for an eight-year period, from 2013 to 2020. Twelve public and private hospitals were involved, including a cancer centre where radiotherapy (RT) and nuclear medicine (NM) procedures are regularly performed. OEWs were monitored, on a monthly or quarterly basis, for whole-body dose and extremity dose using an optically stimulated luminescence (OSL) dosimeter worn on the torso or the wrist, as appropriate. Eye-lens dose was estimated from whole-body dose results. Results: The whole-body dose distribution was skewed and the zero dose was associated with a probability of 47%. Some recorded doses were associated with estimated X-ray energies above those typically encountered in diagnostic radiology, thus suggesting that some doses attributed to workers and believed to be due to X-rays may in fact be due to background radiation (false positive dose records). For the period 2013–2020, annual doses to OEWs in diagnostic radiology (DR), NM and RT departments were 0.40 ​mSv, 0.38 ​mSv and 0.09 ​mSv, respectively. For the same period, the mean annual extremity and eye-lens doses were 0.78 ​mSv (range: 0–5.24 ​mSv) and 0.35 ​mSv (range: 0–3.74 ​mSv), respectively. Conclusion: With little effort by the national IMS and the regulatory body, annual whole-body doses to workers can be kept well below 6 ​mSv, thus efficiently contributing to the optimization of worker's protection. However, extremity doses may in fact be greater than those reported for OEWs in the NM department. Finally, eye-lens doses were well below the new annual dose limit of 20 ​mSv, thus demonstrating that, in the current situation, OEWs in the NM department do not require routine eye lens dose monitoring. Rather, whole-body dose may be used as an indicator of eye-lens dose.